ANALISIS PRAGMATIK TINDAK TUTUR ILOKUSI DALAM UNGGAHAN INSTAGRAM @OFFICIAL_UNILA - Eva Berliana; Sumarti Sumarti; Nurlaksana Eko Rusminto (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to identify and describe the types of illocutionary speech acts found in Instagram posts of @official_unila as a form of digital communication used by an educational institution. This research employs a qualitative approach with a descriptive method. The data consist of texts or captions in posts of the Instagram account @official_unila that contain illocutionary speech acts. Data were collected through documentation by gathering and recording utterances found in the posts. The data were analyzed by identifying and classifying utterances based on Searle’s classification of illocutionary speech acts, including assertive, directive, commissive, expressive, and declarative acts. The results show that there are 25 illocutionary speech acts consisting of 7 assertives, 4 directives, 3 commissives, 7 expressives, and 4 declaratives. Assertive and expressive acts are the most dominant types found in the posts. The findings indicate that the Instagram account @official_unila is not only used to deliver information but also serves as an institutional communication strategy to build relationships with the public and strengthen the university’s image through social media. The novelty of this research lies in analyzing illocutionary speech acts in digital communication of educational institutions through Instagram.